Pengaruh Pembelajaran Kewirausahaan Terhadap Motivasi Kewirausahaan - Zainul Muchlas (RELASI : JURNAL EKONOMI, 2021)
This study aims to give consideration to the decision makers in developing entrepreneurship learning curriculum that can increase student motivation to make entrepreneurship as a career choice. The research was conducted in a Quasi Experiment by comparing entrepreneurial learning that can increase student motivation with high pull factors for entrepreneurship. Entrepreneurship learning methods are expected to encourage students with high pull factors to choose a career as an entrepreneur to alleviate undergraduate / educated unemployment in Indonesia. The learning groups that were compared consisted of Groups A, B, C, D with different learning treatments. Findings This study shows that groups of students with high pull factors who obtain entrepreneurial learning have a significant increase in entrepreneurial motivation between before and after entrepreneurial learning. The highest increase in entrepreneurship motivation is group C and group D has the highest increase.